City profile: Medellin. (April 2018) - Garcia Ferrari, Soledad; Smith, Harry; Coupe, Francoise; Rivera, Helena
Abstract: After being known as the 'murder capital of the world' in the 1990s, Medellin has pioneered innovative forms of city planning and management and was acclaimed the most innovative city in the world by the Urban Land Institute (ULI) in 2013. Hosting the World Urban Forum in 2014 allowed it to showcase its approach, key elements of which have been: creation of innovative transport infrastructure linking poorer peripheral districts to the city centre; culture-led regeneration; strong support of local development from the local business sector; and a successful municipally-owned utilities company. However, the city is spreading outwards without services and employment being provided; new low-income developments are replicating high-rise models which failed worldwide; there is limited intervention in the existing informal areas, many being in highly vulnerable locations where the level of risk is likely to increase with climate change; development has little regard for topography, ecological and environmental considerations; investment in accessible and good quality public space is restricted to some areas; the quality of the public realm does not always support health and wellbeing of the ageing population. This paper explores the institutional and socio-economic context in which Medellín has achieved the internationally recognized status of an 'innovative city'. It questions to what extent social equity, environmental sustainability and citizen empowerment have been promoted as per the ULI claims when it conferred the prize. The paper queries the extent to which 'urban innovation' is happening in Medellín, which has considerable implications given its recently found role as a 'model' city in Latin America and beyond. Highlights: Medellín has pioneered innovative and acclaimed forms of city planning and management in recent years. Culture-led regeneration and innovative transport infrastructure link poorer peripheral districts. Equity, environmental sustainability and citizen empowerment remain to be explored in this 'model city'.